Presencia de bullying y su incidencia en la depresión infantil en niños de 8-12 años, de la escuela de Educación Básica Luis Urdaneta, del cantón Pindal, provincia de Loja, periodo enero-julio 2015 - Apolo Torres, Jessica Elizabeth (2015)
According to OMS (World Health Organization) considered that the Childhood depression occupies the fourth place as cause of morbidity in the world, with high prevalent rates which reaches between 8% and 20% in children and teenagers. Thus the importance to develop this research work, whose objective is to identify bullying presence and its incidence in the child depression on children from 8 to 12 years old, in the Education Basic School Luis Urdaneta of the Pindal Canton of Loja Province. The investigation was the kind of descriptive-transversal, being as it pointed out the relationship between the bullying with the depressive conditions on children and the application of its purpose.It was taken a sample of 190 students to whom where applied the survey about their pre conceptions of peer intimidation and abuse. PRECONCIMEI and the inventory of the Child Depression, CDI which showed basic data that guided the Psychological diagnostic.The PRECONCIMEI, showed the frequent ways of violence in the educative center , establishing verbal manifestations like: taunt or name calling, (67,36%) the but frequent; other way was physical abuse (13,68%), followed by laugh down another child (6,84%).The inventory of Child Depression allowed to determine that the 31% of the sample showed minimum or moderated depression.The numbers allow to conclude that bullying have impact in the Child Depression on investigated children , based on it comes the need of a Psychology intervention throughout an integral treatment , in order to offer therapeutic companion which pursue to the improvement of their emotional states of these children. Key words: Bullying, harassment, Child Depression, Psychology Intervention.